Odpowiedzi

Najlepsza Odpowiedź!
2010-02-18T16:41:39+01:00
A)6xy-5xy+4xy-3xy+2xy-xy = 3xy
b)2,5a-a-4a+6,5a-3,5a = 0,5a
c)0,3x-0,4x+0,5x-0,6x+0,7x = 0,5x
d)696y-696y+69y-96y = -27y
e) ½a² + ⅓a² + ⅙a² - 2a² = ³/₆ a² + ²/₆ a² + ⅙a² - 2a² = ⁶/₆ a² - 2a² = 1a² - 2a² = -a²
2010-02-18T16:44:40+01:00
A)
6xy-5xy+4xy-3xy+2xy-xy = 3xy
b)
2,5a-a-4a+6,5a-3,5a = 0,5a
c)
0,3x-0,4x+0,5x-0,6x+0,7x = 0,5x
d)
696y-696y+69y-96y = -27y
e)
1/2a²+1/3a²+1/6a²-2a² = -a²
2010-02-18T17:53:18+01:00
A)6xy-5xy+4xy-3xy+2xy-xy = 3xy
b)2,5a-a-4a+6,5a-3,5a = 0,5a
c)0,3x-0,4x+0,5x-0,6x+0,7x = 0,5x
d)696y-696y+69y-96y = -27y
e)1/2²+1/3a²+1/6a²-2a ² = -a²